Gay Lives and 'Aversion Therapy' in Brezhnev's Russia, 1964-1982 - Alexander, Rustam (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2023)
This book examines the autobiographies and diaries of Soviet homosexual men who underwent psychotherapy during the period from 1970 to 1980 under the guidance of Yan Goland, a psychiatrist-sexopathologist from Gorky. The examination of these unique and little known documents contributes to our scant knowledge about the practices that many would call a Soviet proto-type of 'aversion therapy'. It also helps us understand the way homosexual people faced "queer dilemmas" of the self and how they sought to reconcile their queer desire with being Soviet. Rustam Alexander is a historian, specializing in Russia and the USSR, who received his PhD from the University of Melbourne, Australia. He is the author of Red Closet: The Hidden History of Gay Oppression in the USSR (2023) and Regulating Homosexuality in Soviet Russia, 1956-91: A Different History (2021). His work on the history of Soviet homosexuality has been publishedin Slavic Review, Russian History, Europe-Asia Studies and other academic journals.
1 : Introduction -- 2 : Yan Goland and His 'Aversion Therapy' -- 3 : Leonid Bykov-An Autobiography -- 4 : Leonid Bykov-Diary -- 5 : Pavel Krotov-An Autobiography -- 6 : Mark Orlov-An Autobiography -- 7 : The Autobiography and Diary of Artem Smirnov -- 8 : Conclusion.
Keywords: Women -- History; Russia -- History; Europe, Eastern -- History; Soviet Union -- History; History, Modern; Sex; Women's History / History of Gender; Russian, Soviet, and East European History; Modern History; Gender Studies